Janus kinase 1 inhibitor INCB054707 for patients with moderate‐to‐severe hidradenitis suppurativa: results from two phase II studies. (1st May 2022) - Alavi, Afsaneh; Hamzavi, Iltefat; Brown, Kurt; Santos, Leandro L.; Zhu, Zhaoyin; Liu, Huiqing; Howell, Michael D.; Kirby, Joslyn S.
Summary: Background: Janus kinase (JAK)‐mediated cytokine signalling contributes to local and systemic inflammation in hidradenitis suppurativa (HS). Objectives: To describe the safety and efficacy results from two multicentre phase II trials of the JAK1 inhibitor INCB054707 in patients with moderate‐to‐severe HS. Methods: Patients received open‐label INCB054707 15 mg once daily (QD; Study 1) or were randomized to INCB054707 30, 60 or 90 mg QD or placebo (3 : 1 within each cohort; Study 2) for 8 weeks. Eligible patients were aged 18–75 years and had moderate‐to‐severe HS (Hurley stage II/III disease), lesions present in at least two anatomical locations, and a total abscess and inflammatory nodule count ≥ 3. The primary endpoint for both studies was safety and tolerability. Secondary endpoints included HS Clinical Response (HiSCR) and other efficacy measures. Results: Ten patients were enrolled in Study 1 (15 mg INCB054707) and 35 in Study 2 (INCB054707: 30 mg, n = 9; 60 mg, n = 9; 90 mg, n = 8; placebo, n = 9). Overall, 70% of patients in Study 1 and 81% of patients receiving INCB054707 in Study 2 experienced at least one treatment‐emergent adverse event; 30% and 42% of patients, respectively, had at least one treatment‐related adverse event. Among the evaluable patients, three (43%) in Study 1 and 17 (65% overall: 30 mg, 56%; 60 mg, 56%; 90 mg, 88%) receiving INCB054707 vs. 4 patients (57%) receiving placebo in Study 2 achieved HiSCR at week 8. Conclusions: INCB054707 was well tolerated, with responses observed in patients with moderate‐to‐severe HS. The safety and efficacy findings from these studies demonstrate proof of concept for JAK1 inhibition in HS. The studies are registered on ClinicalTrials.gov (NCT03569371 and NCT03607487).